Respuesta :

Answer:

  x³ +7x² +7x -15

Step-by-step explanation:

Apply the distributive property repeatedly, and/or recognize the ways that the coefficients of the product are formed.

distributive property

  (x -1)(x +3)(x +5)

  = (x -1)(x(x +5) +3(x +5))

  = (x -1)(x² +5x +3x +15) = (x -1)(x² +8x +15)

  = x(x² +8x +15) -1(x² +8x +15)

  = x³ +8x² +15x -x² -8x -15

  = x³ +7x² +7x -15

__

using knowledge of products of powers

The x³ term will be the product of all of the x-terms.

The x² term will be the pairwise sum of products of two x-terms and the third constant.

The x term will be the pairwise sum of products of one x-term and the two other constants.

The constant term will be the product of all of the constants.

These computations are simplified a bit because all of the x-coefficients are 1.

  = x³ +(-1 +3 +5)x² +(-1·3 +(-1)·5 +3·5)x +(-1)·3·5

  = x³ +7x² +7x -15

ACCESS MORE